1)
3x-y=2
2x+2y=5
y=3x - 2
2x+2(3x - 2)=5
y=3x - 2
2x + 6x - 4 = 5
y=3x - 2
8x=9
y=3x - 2
x= 9/8
y=3* 9/8 - 2
x= 9/8
y = 11/8
x = 9/8
Проверка
3 * 9/8 - 11/8 = 2
27/8 - 11/8 = 2
16/8 = 2
2=2
2)
3x-5y=4
2x+6y=3
5x + y = 7
2x + 6y = 3
y= 7- 5x
2x + 6y = 3
y= 7 - 5x
2x + 6(7-5x) = 3
y= 7 - 5x
2x + 42 - 30x = 3
y= 7 - 5x
42 - 3 = 30x - 2x
y= 7 - 5x
28x = 39
y= 7 - 5x
x = 39/28
y= 7 - 5* 39/28
x= 39/28
y= 196/28 - 195/28
x = 39/28
y=1/28
x=39/28
Проверка
3* 39/28 - 5* 1/28 = 4
117/28 - 5/28 = 4
112/28 = 4
4 = 4
3)
4x+3y=2
5x-2y=3
9x + y = 5
5x - 2y = 3
y= 5 - 9x
5x - 2* (5 - 9x) = 3
y= 5 - 9x
5x - 10 + 18x = 3
y= 5 - 9x
23x = 3 + 10
y= 5 - 9x
23x = 13
y= 5 - 9x
x=13/23
y= 5 - 9* 13/23
x= 13/23
y= 115/23 - 117/23
x = 13/23
y= -2/23
x= 13/23
Проверка
4* 13/23 + 3* (-2/23) = 2
52/23 - 6/23 = 2
46/23=2
2=2